Effect of Ambivalent Anxiety Attachment to Children Victims of Sexual Violence in Karawang - Dimala, Cempaka Putrie; Evantri, Elycita (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at determining how the effect of ambivalent anxiety attachment to children victims of sexual violence in Karawang. Subjects consisting of two children with the age of 12 years, are victims of sexual violence, residing in Karawang, have an ambivalent anxious attachment pattern with parents. Researchers working with the P2TP2A Karawang regency to retrieve data, data taken is data reports from 2016-2017. The method used in this research using a qualitative method with a case study approach. Data collection uses non-participants and interviews on subjects and significant people as data triangulation. The results showed the definition of children who had an ambivalent anxiety attachment pattern to parents and became victims of sexual violence made the children have a closed characteristic, less adaptable and took a long time in expressing or telling about the violence they experienced, as well as the feeling that the triggered compilation takes place.